Indonesia's Opportunities and Challenges in IK-CEPA: Bilateral Free Trade Agreement with South Korea - Maulidita, Salismi Zulfi; Darmanto, Darmanto (Insignia: Journal of International Relations, 2024)
The IK-CEPA was officially implemented in 2023 as a commitment between Indonesia and South Korea to cooperate in marketing and fulfil commodity needs, aiming for better and more sustainable economic development. This paper seeks to investigate the opportunities and challenges faced by Indonesia in implementing the IK-CEPA. The comparative method is applied to analyze the secondary data sourced from official publications on bilateral agreements between the two countries, and statistical data on investment, trade, and the country’s trade balance. A comparative data analysis was conducted by comparing the IK-CEPA with the previously implemented free trade agreement (FTA) in Indonesia with similar values, namely the IA-CEPA. In this paper, the IA-CEPA serves as a crucial point of comparison from which analytical results concerning the potential opportunities or challenges of the IK-CEPA were derived, focusing on several indicators like foreign direct investment (FDI) flow, trade value, and trade balance. The results show that Indonesia has the opportunity to: (1) increase the FDI value; (2) increase trade values with South Korea; and (3) improve the trade balance with South Korea to achieve a surplus. Two challenges for Indonesia in this endeavor include failure to achieve a trade balance surplus and the need for maximum utilization of the IK-CEPA by the Micro, Small and Medium Enterprises (MSMEs). Keywords: bilateral cooperation, comparative analysis, free trade agreement, IK-CEPA